Analysis of Land Capability for Potential Disasters in Banjarnegara Regency, Central Java - Alfarizi, M. Zaky; Salsabila, Sonia Nada; Matoka, Mayselina Candra Rahman; Fajarwati, Alia (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Land capacity includes the physical components that influence the potential for disasters in an area. Land capacity classification can provide a systematic assessment of land through categories of characteristics that are potential as well as obstacles to its sustainable use. One example of inhibiting factor is disaster, so the aim of this research is to find out areas that are vulnerable and the level of regional capacity in dealing with natural disasters. The existence of a land capability classification can provide a systematic assessment of land so that it can categorise it as potential or obstacle to land use. This research method is scoring and weighting which is based on Public Planning and Public Housing (PUPR) Ministerial Decree No. 20 of 2007 combined with practical teaching materials for land use planning, Faculty Geography, Universitas Gadjah Mada. There are 4 data inputs, natural disaster maps, slope, rain intensity, and soil sensitivity to erosion. Each input has a variable range that varies on a scale at levels 1-5 with weight range of 0-100. The research location is in Banjarnegara Regency, Central Java. The results obtained are the level of regional capacity for natural disasters in each sub-district, including very low, low, medium, high and very high land capacity with different intensities in each region. Erosion and landslides and landslides are the ratio of disasters with a relatively large area compared to erosion disasters. Apart from that, areas that do not fall into either category are included in the category of areas that are safe from disasters.